Analisis Proses Pengiriman Pesan VMS (Variable Message Sign) pada Lima Ruas Jalan Tol Jabodetabek - Fenty Tristanti Julfia; Eka Satryawati; Dedy Setiadi; Wiga Ariani; Regeng Rijadi (Journal on Education, 2023)
Precise, fast and accurate information regarding traffic density conditions is what toll road users need. Toll road users can choose a route that is faster, smoother and safer to pass through information on the traffic conditions of the toll road to be passed in front of them, which is conveyed from the Variable Message Sign (VMS). Given the very dynamic traffic conditions in Jabodetabek and Bandung, a very reliable media and information technology support is needed, so that it can provide information on real traffic conditions, precisely according to conditions in the field. This information can be retrieved from Google Maps periodically as needed to update information on traffic conditions in the segments that will be displayed on the VMS. The segment is usually the distance from gate 1 to the next gate, or Interchange 1 to the next Interchange. The period of retrieval of information via Google Maps depends on the dynamics of traffic conditions that will be displayed on the VMS. For example, information related to traffic conditions for the Tomang – Kebon Jeruk segment, which is very dynamic, requires a shorter period of change or information update than the Kunciran – Parigi or Kunciran – Serpong segments, the period of each information change is longer or infrequent, because the traffic conditions are still small. VMS will display the information generated through the distance and average travel time from 1 point to a certain point in 1 segment of the toll road which is processed so as to produce the average vehicle speed data which will be converted into text that will be displayed on the VMS. The text formatted information is sent to the VMS. The process of withdrawing Google Maps data to sending text to VMS can be done in less than 1 minute, even the process can be carried out for more than 1 VMS and even 10 VMS units in 1 minute. This results in fast and accurate information.